2021
DOI: 10.18502/jbe.v7i2.6737
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Challenges of Information Fusion Technique for Big Data Analysis: Proposed Framework

Abstract: Introduction: Recently, with the surge in the availability of relevant data in various industries, the use of Information Fusion technique for data analysis is increasing. This method has several advantages, such as increased accuracy, and the use of meaningful information. In addition, there are certain challenges, including the impact of data type and analytical method on results. The goal of this study is to propose a framework for introducing the advantages and classifying the challenges of this technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Since the emergence of big data, it has been respected by all sectors of society [10] and has been quickly applied to all aspects of social development. Using big data technology to measure and analyze the world, and to mine the potential value of the data itself by analyzing the correlation of the data, so as to better promote the development of society [11].…”
Section: E Meaning Of Big Data and Its Development Historymentioning
confidence: 99%
“…Since the emergence of big data, it has been respected by all sectors of society [10] and has been quickly applied to all aspects of social development. Using big data technology to measure and analyze the world, and to mine the potential value of the data itself by analyzing the correlation of the data, so as to better promote the development of society [11].…”
Section: E Meaning Of Big Data and Its Development Historymentioning
confidence: 99%
“…Kim, Ku [36] used SVM to predict the rise and fall of individual stocks and verified the effectiveness of SVM in classifying the rise and fall of individual stocks through empirical analysis. Lahmiri [37] compared the performance of ANN and SVM in predicting stock movements and found that ANN outperformed SVM in terms of prediction accuracy, and feedforward ANN has been widely used due to its ability to predict both upward and downward movements of stocks as well as stock prices [38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, the current study relies on a single stock-related information source, which may limit the predictive power of the proposed model. Indeed, stock markets are typically influenced by a variety of textbased information sources, such as monetary news, online media, websites, or corporate statements [8,14,31,38,51,52]. These information sources differ in the way they influence monetary economic entities.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Therefore, machine learning methods, which are a sub eld of arti cial intelligence that provides computers with the ability to learn without having to be explicitly programmed, have become an increasingly popular tool for medical researchers. By applying these techniques, patterns and relationships can be discovered and identi ed from complex datasets, while they are capable of predicting future outcomes of a given type of cancer (10)(11)(12)(13)(14). As a result, these techniques have become increasingly popular and various biomarkers have been identi ed for the diagnosis, prognosis, and treatment of a wide range of cancers, including breast cancer, prostate cancer, pancreatic cancer, and colorectal cancer in recent years (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%